2,4-Dichloro-1-[1-(2,4-dichlorobenzyloxy)ethyl]benzene - Jasinski, Jerry P. (International Union of Crystallography, 2009)
In the title compound, C(15)H(12)Cl(4)O, the dihedral angle between the least-squares planes of the two benzene rings is 82.6 (9)°. The dihedral angles between the COC mean plane of the oxy group and the two benzene rings are 84.3 (5) and 10.8 (5)°. In the crystal, two weak π–π interactions [centroid–centroid distances = 3.9989 (8) and 3.7912 (8) Å] and a C—H⋯π interaction are observed.